Inulin Amphiphilic Copolymer-Based Drug Delivery: Unraveling the Structural Features of Graft Constructs - Carla Sardo; Giulia Auriemma; Carmela Mazzacano; Claudia Conte; Virgilio Piccolo; Tania Ciaglia; Marta Denel-Bobrowska; Agnieszka B. Olejniczak; Donatella Fiore; Maria Chiara Proto; Patrizia Gazzerro; Rita Patrizia Aquino (MDPI AG, 2024)
In this study, the structural attributes of nanoparticles obtained by a renewable and non-immunogenic "inulinated" analog of the "pegylated" PLA (PEG-PLA) were examined, together with the potential of these novel nanocarriers in delivering poorly water-soluble drugs. Characterization of INU-PLA assemblies, encompassing critical aggregation concentration (CAC), NMR, DLS, LDE, and SEM analyses, was conducted to elucidate the core/shell architecture of the carriers and in vitro cyto- and hemo-compatibility were assayed. The entrapment and in vitro delivery of sorafenib tosylate (ST) were also studied. INU-PLA copolymers exhibit distinctive features: (1) Crew-cut aggregates are formed with coronas of 2-4 nm; (2) a threshold surface density of 1 INU/nm2 triggers a configuration change; (3) INU surface density influences PLA core dynamics, with hydrophilic segment stretching affecting PLA distribution towards the interface. INU-PLA2NPs demonstrated an outstanding loading of ST and excellent biological profile, with effective internalization and ST delivery to HepG2 cells, yielding a comparable IC50.